PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP PRESTASI BELAJAR IPA SISWA KELAS V SD NEGERI GEDONGTENGEN YOGYAKARTA TAHUN AJARAN 2016/2017 - Anisa Eka Pratiwi; Yuli Prihatni (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract: This study descriptively aims to know the category of achievement of science subject by using cooperative learning model byÂ  teams games tournamentÂ  type andÂ  conventionalÂ  model. Comparatively to know the difference of learning achievement of science subjectÂ  byÂ  using cooperative learning model byÂ  teamsÂ  gamesÂ  tournamentÂ  typeÂ  andÂ  conventionalÂ  model.Â  TheÂ  typeÂ  ofÂ  thisÂ  studyÂ  wasÂ  quasi experiment. Data collection techniques used test and documentation. Data analysis techniques used descriptive analysis and hypothesis testing by using t test that was started by homogeneity variant test and normality test. This study shows that the scoreÂ  ð‘¡hitungÂ  =Â  3,665Â  and the score of p = 0,001. Thus,Â  itÂ  can Â concludeÂ  thatÂ  thereÂ  wasÂ  significantÂ  differenceÂ  ofÂ  learningÂ  achievementÂ  science.Â  The average score of learning achievement science that using cooperative learning model by teams games tournamentÂ  typeÂ  wasÂ  higherÂ  thanÂ  conventionalÂ  model.Â  It Â meansÂ  thatÂ  thereÂ  areÂ  influencesÂ  of cooperative learning model by teams games tournament type toward learning achievement science.